A correlation between pavement skid resistance and wet-pavement related accidents in Thailand. - Jumrus Pitaksringkarn; Ladda Tanwanichkul; Kwanruen Yamthale (My University, 2018)
This research aims to study a correlation between a pavement skid resistance and wet-pavement related accidents in order to determine the minimum friction threshold so called ’Investigatory Level (IL)’ for the roads in Thailand. An accident database, a skid resistance database and a traffic volume of road network from the department of Highways, totalling 19 routes and 386kilometers, were used in the analysis of this study. In the analysis, 500-meter subsection intervals are used to determine a correlation between an average pavement skid resistance and wet-pavement accident rate using a non-linear regression analysis model. It was discovered that the pavement skid resistance has a major influence on the accident rate, depending on various types of road geometry. Moreover, the preliminary investigatory level is determined by using a past accident rate information as a reference for an investigatory level basis. We discover that the single carriageway (non-event) road is at highest threat due to low pavement skid resistance. The recommended investigatory level for each of the five road geometries all site, single carriageway, dual carriageway, horizontal alignment and curve road categories are 035, 0.50, 0.30, 0.30, and 0.40, respectively, which are in accordance to the investigatory level values in other countries.
Keywords: Skid (aerodynamics); Carriageway; Asphalt Pavement Performance Evaluation